Selectivity of acephate and propaphos to the wolf spider, Pardosa pseudoannulata (Boes et Strand) and brown planthopper, Nilaparvata lugens (Stal). Part II. Metabolism - Thang, M.H.; Morallo-Rejesus, B.; Shepard, B.M. (2000)
The activation and detoxification of acephate and propaphos in the predatory wolf spider, Pardosa pseudoannulata, and its prey, the brown planthopper, Nilaparvata lugens, were investigated. The rate of penetration, distribution, and excretion of these insecticides and their metabolites were also examined. Acephate was mainly metabolized to a potent AChE inhibitor, methamidophos, by N. lugens but not by P. pseudoannulata. Propaphos was metabolized into active metabolites, propaphos sulfoxide and propaphos sulfone, by N. lugens and P. pseudoannulata. However, further degradation of these metabolites into non-toxic compounds was higher in the latter than in the former. The metabolic pathways of acephate and propaphos in N. lugens and P. pseudoannulata are proposed. Both acephate and propaphos underwent slower penetration, poorer internal accumulation, and higher excretion in P. pseudoannulata than in N. lugens. The mechanisms for selectivity of acephate and propaphos to P. pseudoannulata could be attributed to the lower rate of bioactivation to potent AChE inhibitors, coupled with rapid degradation of the active metabolites, reduced rate of penetration and internal accumulation, and rapid excretion of unchanged acephate or metabolites of propaphos compared to N. lugens.
Keywords: Spiders; Metabolism; Pesticide toxicology